Synopsis of the distribution of the rare tiger beetle Opisthencentrus dentipennis (Coleoptera: Cicindelidae) - Roza, André Silva (Zootaxa, 2022)
Opisthencentrus W. Horn, 1893 is a rare monotypic genus of Cicindelidae. The only species, Opisthencentrus dentipennis (Germar, 1843), was recently revised, based only on seven historical specimens, besides a recent published record. The objective of this paper is to provide an updated synopsis of the distribution of Opisthencentrus through the examination of recently collected material. Specimens were examined from several important Brazilian collections to understand the genus distributional range. An updated distribution and distributional map for O. dentipennis is presented based on the examination of 12 specimens, 7 recently collected. The species occurs in a relatively large area of the Atlantic Rainforest, covering from the Serra dos Órgãos, in Rio de Janeiro State, to the Alto da Serra de Paranapiacaba, in Santo André, São Paulo State. It can also endure an altitudinal amplitude of 1100m from the lowest to the highest record. The rather large distribution of the species contrasts with its scarcity in collections, raising questions about the best sampling method for it, the species life cycle duration, or the species populations, which may be reduced due to deforestation or sensitivity to a particular factor.